Utilizing PVSyst for planning a hybrid system rooftop solar power plant at Makassar Eye Hospital - Sonong, Sonong; Yunus, A.M. Shiddiq; Djalal, Muhammad Ruswandi; Sianturi, Farhan; Purnama, Rahma; Takdir, Ahmad (Universitas Mercu Buana, 2024)
Installing rooftop Solar Power Plants (SPP) represents the most efficient solution for reducing substantial electricity consumption in office buildings and hospitals, as Makassar Eye Hospital exemplifies. The research commences by addressing concerns about electricity availability and daily usage at the hospital while evaluating the solar radiation potential. Subsequently, the development of the SPP system begins. A location assessment is conducted using various tools to gather the necessary data for SPP design. In this study, the planning phase involves the utilization of PVSyst software for the technical analysis of electrical energy generation and system performance calculations. Additionally, the economic analysis includes evaluating the initial investment costs for establishing the SPP and considering prevailing market prices for components. The feasibility of the SPP investment is determined by calculating key financial metrics, including the Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), and Return on Investment (ROI). According to the economic analysis findings, the initial investment cost for the SPP amounts to Rp. 544.031.733. The energy production value per kilowatt-hour (kWh) stands at Rp. 1.278, resulting in a Payback Period (PP) of 13,8 years, a Net Present Value (NPV) of Rp. 138.182.638, an Internal Rate of Return (IRR) of 11.51%, and a Return on Investment (ROI) of 25.4%. These results affirm the plan's feasibility, as the IRR value surpasses the Discount Rate (8.43%).